2020
DOI: 10.1038/s41598-020-73233-7
|View full text |Cite
|
Sign up to set email alerts
|

Pre-clinical dose-ranging efficacy, pharmacokinetics, tissue biodistribution, and toxicity of a targeted contrast agent for MRI of amyloid deposition in Alzheimer’s disease

Abstract: In these preclinical studies, we describe ADx-001, an Aβ-targeted liposomal macrocyclic gadolinium (Gd) imaging agent, for MRI of amyloid plaques. The targeting moiety is a novel lipid-PEG conjugated styryl-pyrimidine. An MRI-based contrast agent such as ADx-001 is attractive because of the lack of radioactivity, ease of distribution, long shelf life, and the prevalence of MRI scanners. Dose-ranging efficacy studies were performed on a 1 T MRI scanner using a transgenic APP/PSEN1 mouse model of Alzheimer’s dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 38 publications
(49 reference statements)
0
24
0
Order By: Relevance
“…Delayed post-contrast MRI was performed 4 days later. MR images were acquired using a T1-weighted spin-echo (T1w-SE) sequence and a T1-weighted fast spin echo inversion recovery (FSE-IR) sequence 46 . Transgenic mice administered TauT1 and TauT3 demonstrated signal enhancement in the cortex and the hippocampus regions of the brain ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Delayed post-contrast MRI was performed 4 days later. MR images were acquired using a T1-weighted spin-echo (T1w-SE) sequence and a T1-weighted fast spin echo inversion recovery (FSE-IR) sequence 46 . Transgenic mice administered TauT1 and TauT3 demonstrated signal enhancement in the cortex and the hippocampus regions of the brain ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Coil calibration, RF calibration, and shimming were performed at the beginning of study for each subject. The pre-contrast scans provide a baseline for calculation of signal enhancement from resulting post-contrast scans 46 . Two-standard deviations above the mean variation within WT control animals was used as the cutoff signal intensity for identifying tau positive animals.…”
Section: Methodsmentioning
confidence: 99%
“…Chelates of Gadolinium (Gd), Gd 3+ is usually available as standard T1 (longitudinal) MRI contrast agents. In addition, the use of Gd-based small molecules [ 128 , 129 ] and Gd ions in NPs have been used in imaging applications [ 130 , 131 ]. More details about these contrast agents can be found in the interesting reviews by Ulanova et al [ 125 ] and Sharma et al [ 124 ].…”
Section: In Vivo Imaging Detection Platforms Of Ad Using Plasmonicmentioning
confidence: 99%
“…ADx-001 was tested at three dose levels to determine the effect of contrast agent dose on the detection of amyloid plaques in vivo. Conventional MR metric of signal enhancement (percentage change between pre-and postcontrast MRI) demonstrated excellent performance at 0.2 mmol Gd/kg dose but suboptimal performance (< 0.7) at lower dose levels (0.15 and 0.1 mmol Gd/kg) [3]. In this study, we examined if nano-radiomics (radiomic analysis of nanoparticle contrast-enhanced images) could augment performance at lower dose levels of ADx-001 for detection of amyloid pathology in mice with higher plaque burden.…”
Section: Introductionmentioning
confidence: 95%
“…Studies have also indicated that certain brain regions such as the cerebral cortex and hippocampus are more vulnerable to AD than other regions, which may be related to the memory deficits observed in human AD [2]. In our previous preclinical work, we examined the efficacy of an amyloid targeted liposomal macrocyclic gadolinium contrast agent (ADx-001) for in vivo molecular MRI of amyloid pathology in a mouse model of Alzheimer's disease with high plaque burden [3]. ADx-001 was tested at three dose levels to determine the effect of contrast agent dose on the detection of amyloid plaques in vivo.…”
Section: Introductionmentioning
confidence: 99%